STRATEGI KREATIF PRODUSER PROGRAM JEJAK ANAK NEGERI EPISODE NAPAK PERTIWI DALAM MENGEMAS KONTEN BUDAYA - I Putu Suhada Agung (Texture: Visual Art and Culture Journal, 2023)
This study discusses the creative strategies implemented by producers in packaging cultural content in the Napak Pertiwi episode of Jejak Anak Negeri program in TRANS7. This research method uses a qualitative descriptive approach with data collection techniques through interviews with producers and assistant producers as well as making observations through broadcast copies on the youtube channel and the official social media of Jejak Anak Negeri. The producer’s creative strategy is analyzed using 13 creative strategy elements based on the book by Naratama.